2008
DOI: 10.1007/s00431-008-0714-1
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma pneumoniae: nervous system complications in childhood and review of the literature

Abstract: Mycoplasma pneumoniae is an important pathogen which causes nervous system disorders during or after the course of a respiratory tract infection. The exact pathogenic mechanism which causes neurological disorders still remains unknown. Although meningoencephalitis and acute disseminated encephalomyelitis are common complications, there are few cases of acute transverse myelitis and isolated abducens nerve palsy associated with M. pneumoniae infection in childhood. The association between ocular myasthenia grav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 34 publications
0
39
0
8
Order By: Relevance
“…Direct invasion of the CNS, auto immunologic effects, vascular injury, and neurotoxin involvement are discussed. 4,6,8,10,14,15 In a recent study by Meyer Sauteur et al the CSF of seven M. pneumoniae-associated encephalitis cases who previously had been suffering from respiratory symptoms was investigated. PCR was performed in all patients with negative results in all.…”
Section: Discussionmentioning
confidence: 99%
“…Direct invasion of the CNS, auto immunologic effects, vascular injury, and neurotoxin involvement are discussed. 4,6,8,10,14,15 In a recent study by Meyer Sauteur et al the CSF of seven M. pneumoniae-associated encephalitis cases who previously had been suffering from respiratory symptoms was investigated. PCR was performed in all patients with negative results in all.…”
Section: Discussionmentioning
confidence: 99%
“…Les présentations à type de myosite ont en revanche rarement été décrites (moins d'une dizaine de cas) [15]. M. pneumoniae serait éga-lement la première cause de névrite optique identifiée chez l'enfant [16], la paralysie du nerf abducens restant la forme la moins décrite [17,18]. D'un point de vue pronostique, une revue ancienne de formes neurologiques avait rapporté un tiers de séquelles indépendamment du mode de présentation [19].…”
Section: Discussionunclassified
“…Because of its diverse distribution of affected areas, an indirect mechanism has been postulated, namely, immune complexmediated vasculopathy [Behan et al, 1986;Guleria et al, 2005;Gupta et al, 2009]. On the other hand, recent studies on patients with acute disseminated encephalomyelitis have demonstrated the presence of M. pneumoniae genome in the cerebrospinal fluid [Matsumoto et al, 2009;Riedel et al, 2001;Yiş et al, 2008], or the presence of M. pneumoniae antigens inside the macrophages in the brain tissue [Stamm et al, 2008]. Thus it is highly possible that a direct mechanism, namely, vasculitis as a consequence of cytokine activation by M. pneumoniae, is responsible for some instances of acute disseminated encephalomyelitis.…”
Section: Acute Disseminated Encephalomyelitismentioning
confidence: 99%